Blue ocean strategy environmental variables, and performance of four and five stars hotel in Kuala Lumpur, Selangor, and Putrajaya, Malaysia / Mohd Farih Mat Yasin - Mat Yasin, Mohd Farih (2018)
Attaining remarkable performance is one of the essential goals of any hotel due to worldwide rivalry. A successful organization continually reinvents strategies in order to gain better performance and competitive advantages in today‟s dynamic competition. Understanding important environmental factors and generating relevant information and strategic planning can contribute to performance improvement. Compatibility between environmental dimensions and strategic orientation will lead to superior performance.